(untitled) (American Journal of Islam and Society, 2012)
Using ideas from New Institutional Economics (NIE), this paper examines the Islamization of economies and links it to the Islamization of knowledge. NIE uses a multi-disciplinary approach to explain how economic structures evolve and change over time. These structures are studied at four levels: cultural, institutional, organizational, and transactional. While culture embodies a given society’s body of knowledge, the nature and growth of that knowledge determine the type and evolution of an economy’s institutions, organizations, and transactions. This paper contends that the Islamization of economies failed mainly due to a lack of the Islamic knowledge needed to produce the appropriate institutions and organizations. After examining the status of knowledge in the Muslim world, examples of legal institutions are presented to illustrate how dormant Islamic scholarship led to economic structures that lack an Islamic ethos. Establishing an Islamic economic structure would require reorienting an Islamic society’s culture via the creation of new Islamic knowledge that can build appropriate institutions, organizations, and transactions.